(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Translation involves more than word-for-word conversion; it requires understanding language, culture, and context. Strategies like direct translation, borrowing, modulation, adaptation, and calque help convey meaning accurately while maintaining cultural relevance. Effective translation balances fidelity to the source with clarity and appropriateness for the target audience.